THE SPECIFICITY OF RESPIRATORY PIGMENTS - GIRAL, JOSE (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1940)
The possible origin of life from volcanic emanations is considered Volcanic sulfur, especially from Popocatepetl, was examined Structures resembling protozoan and 1-celled algal species, very much like those already obtained in the laboratory, were disc
CIENC MEX
Keywords: SPECIFICITY, RESPIRATORY, PIGMENTS; CIENCIAS MEDICAS